Survey of cyanobacterial toxins in Czech water reservoirs--the first observation of neurotoxic saxitoxins - Jančula, Daniel; Straková, Lucie; Sadílek, Jan; Maršálek, Blahoslav; Babica, Pavel (Environmental science and pollution research international, 2014)
The environmental occurrence and concentrations of cyanobacterial toxins (cyanotoxins) were investigated in the Czech Republic. Concentrations of microcystins (MCs), cylindrospermopsin (CYN) or saxitoxins (STXs) were determined immunochemically by ELISA assays in 30 water samples collected from the surface layers of 19 reservoirs during the summer season of 2010. MCs were detected in 18 reservoirs and 83 % of samples, with median and maximal concentration being 1.5 and 18.6 μg/L, respectively. The high frequency of MC occurrence coincided with prevalence of cyanobacterium Microcystis sp., which was detected in 87 % samples, followed by Dolichospermum (Anabaena) sp. observed in 33 % samples. CYN was detected by ELISA only in one sample at a concentration of 1.2 μg/L. STXs presence was indicated for the first time in Czech water reservoirs when the toxins were found at low concentrations (0.03-0.04 μg/L) in two samples (7 %) collected from two different reservoirs, where STXs co-occurred with MCs and eventually also with CYN. In both STX-positive samples, the phytoplankton community was dominated by Microcystis sp., but Dolichospermum sp. and/or Aphanizomenon sp. were also present as putative producers of STX and/or CYN. Cyanotoxins commonly occurred in Czech water reservoirs, and MCs frequently at concentrations possibly associated with human health risks. MCs were the most prevalent and abundant cyanotoxins, but also other cyanotoxins were detected, though sporadically. Further research and regulatory monitoring of cyanotoxins other than MCs is therefore required.
Keywords: Phytoplankton; mikrocystiny; Cyanobacteria; Enzyme-Linked Immunosorbent Assay; sinice; Saxitoxin; neurotoxiny; mořské toxiny; Bacterial Toxins; monitorování životního prostředí; Aphanizomenon; Anabaena; Microcystins; saxitoxin; zásobování vodou; uracil; Fresh Water; Neurotoxins; Microcystis; ELISA; sladká voda; Czech Republic; Marine Toxins; Environmental Monitoring; Uracil; bakteriální toxiny; Česká republika; Water Microbiology; Water Supply; fytoplankton; mikrobiologie vody